2023
DOI: 10.1021/acs.jmedchem.3c00195
|View full text |Cite
|
Sign up to set email alerts
|

Development of the High-Affinity Carborane-Based Cannabinoid Receptor Type 2 PET Ligand [18F]LUZ5-d8

Abstract: The development of cannabinoid receptor type 2 (CB2R) radioligands for positron emission tomography (PET) imaging was intensively explored. To overcome the low metabolic stability and simultaneously increase the binding affinity of known CB2R radioligands, a carborane moiety was used as a bioisostere. Here we report the synthesis and characterization of carborane-based 1,8-naphthyridinones and thiazoles as novel CB2R ligands. All tested compounds showed low nanomolar CB2R affinity, with (Z)-N-[3-(4-fluorobutyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Dynamic PET scans in rodents revealed a fast uptake in the spleen and liver, a fast hepatic clearance, and non-displaceable binding in the spleen. The overall increase in metabolic stability while maintaining high affinity and selectivity is a valuable starting point for future optimizations for CB2R PET ligands . Moldovan et al report [ 18 F] 5 (Figure ) with high affinity toward human CB2R (hCB2R) and no or low affinity for rat CB2R.…”
Section: Radiopharmaceuticals For Brain Imagingmentioning
confidence: 99%
“…Dynamic PET scans in rodents revealed a fast uptake in the spleen and liver, a fast hepatic clearance, and non-displaceable binding in the spleen. The overall increase in metabolic stability while maintaining high affinity and selectivity is a valuable starting point for future optimizations for CB2R PET ligands . Moldovan et al report [ 18 F] 5 (Figure ) with high affinity toward human CB2R (hCB2R) and no or low affinity for rat CB2R.…”
Section: Radiopharmaceuticals For Brain Imagingmentioning
confidence: 99%
“…The overall increase in metabolic stability while maintaining high affinity and selectivity is a valuable starting point for future optimizations for CB2R PET ligands. 5 Moldovan et al report [ 18 F]5 (Figure 1) with high affinity toward human CB2R (hCB2R) and no or low affinity for rat CB2R. PET scans of a rat model with local hCB2R overexpression demonstrated that [ 18 F]5 was able to selectively and reversibly image cerebral CB2R.…”
Section: ■ Radiopharmaceuticals For Brain Imagingmentioning
confidence: 99%
“…Icosahedral closo-dicarbadodecaboranes (carboranes) have been a focus of interest of many research groups in the past years as building blocks for applications in medicinal chemistry, [1][2][3][4] metal complexes, [5][6][7] supramolecular assemblies, macrocyclic molecules, [8] and luminescent materials. [9,10] Important modifications of carboranes include functionalization of both, boron and carbon vertices, which are influenced by two fundamental electronic properties: the electron delocalization and the electron-withdrawing character of the skeletal carbon atoms.…”
Section: Introductionmentioning
confidence: 99%